Significantly Enhanced Photocatalytic CO2 Reduction by Surface Amorphization of Cocatalysts. Issue 45 (24th September 2021) - Chen, Qin; Mo, Weihao; Yang, Guodong; Zhong, Shuxian; Lin, Hongjun; Chen, Jianrong; Bai, Song
Abstract: Rational phase engineering of reduction cocatalyst offers a promising route to modulate the photocatalytic activity and selectivity in the conversion of CO2 to chemical feedstocks. However, it remains a great challenge to choose a suitable phase given that high‐crystallinity phase is more conducive to the charge transfer and separation, while amorphous phase is more favorable for the adsorption and activation of CO2 molecules. To resolve this dilemma, herein, with Pd as a well‐defined model, a surface amorphization strategy has been developed to fabricate crystalline@amorphous semi‐core‐shell cocatalysts based on the transformation of outer layer atoms of crystalline cocatalysts to disorder phase. According to the theoretical and experimental analysis, in the heterostructured cocatalysts, crystalline core shuttles the photoexcited electrons from light‐harvesting semiconductor to amorphous shell due to its strong electronic coupling with both components. Meanwhile, amorphous shell provides efficient active sites for preferential activation and conversion of CO2 and suppression of undesirable proton reduction. Benefiting from the synergistic effects between crystalline core and amorphous shell, the optimized heterophase cocatalyst with suitable thickness of amorphous shell achieves superior CO (22.2 µmol gcat −1 h −1 ) and CH4 (38.1 µmol gcat −1 h −1 ) formation rates with considerable selectivity and high stability in comparison with crystalline and amorphous counterparts. Abstract : The authors demonstrate a surface amorphization engineering on crystalline cocatalysts for significantly enhanced photocatalytic performance in CO2 reduction. Well‐defined crystalline@amorphous semi‐core‐shell cocatalysts are fabricated, in which crystalline core smoothens the transfer of photoelectrons from semiconductor supporter to amorphous shell, while amorphous shell supplies highly active and selective sites for the CO2 ‐to‐CO/CH4 conversion.